Association of Reading Comprehension and Science Aptitude with Early Success in a First-Semester BSN Cohort: A Cross-Sectional Study. - Torregosa, Marivic B.; Patricio, Orlando (Nursing Reports, 2025)
Background: As the United States population becomes increasingly diverse, the representation of minorities in health professions is critical to addressing health disparities. Few investigations have been conducted among students enrolled in the first semester of the nursing program, a vulnerable and adjustment period for most nursing majors. Thus, this study examined the association between reading comprehension and science aptitude on student retention and standardized test scores. Method: A cross-sectional repeated measures study was conducted to investigate the outcomes from a compendium of programmatic interventions implemented among n = 80 nursing students enrolled in the first semester of a pre-licensure baccalaureate nursing program in one Hispanic-serving institution. These interventions included the Weaver™ reading online program, case studies, NCLEX-type practice tests, test-taking skills, and peer-mentoring. Data collection was conducted in Spring 2024. Multivariate statistical analysis was used to determine predictors associated with student retention and standardized test scores. An independent t-test was used to examine any significant difference in the reading comprehension level among the cohort's participants. A qualitative investigation using thematic analysis was conducted to understand students' experiences with the programmatic interventions. Results: Students' baseline reding comprehension level was significantly associated with failure in the first semester of the nursing program (β = −0.815; SE = 0.349; Wald = 5.444; p < 0.05). End-of-term reading comprehension level was significantly associated with end-of-course HESI score in the Foundations in Nursing course (β = 26.768; SE = 10.049; Beta = 0.445; p < 0.05) while science GPA was significantly associated with end-of-course HESI score for Health Assessment (β = 3.022; SE = 1.315; Beta = 0.434; p < 0.05. Cohort retention was 75%. The independent t-test result indicated a significant difference in reading level was found between those who dropped out from the cohort (M = 4.23, SE = 0.173 and those who did not (M = 5.15, SE = 0.188), t (68) = −3.037, p < 0.01. A reading level of grade 10 and above was associated with student progression to the next semester (M = 10.16, SE = 0.375, t (70) = −0.560, p < 0.05. Although the participants found the reading comprehension modules tedious, test-taking strategies, applying the nursing process in case studies, and the expertise of a nurse educator, who understood the learning needs of first-semester students, were perceived as critical to academic success. Conclusions: Reading comprehension and science aptitude are essential to students' early success in the nursing program. Addressing gaps in reading comprehension and science aptitude before admission to a nursing program would increase chances of success in the early stages of a nursing major.